No grater crime ebook - Day, Maddie (Country Store Mystery, 2021)
Robbie Jordan's Pans 'N Pancakes boasts delicious eats and the best vintage cookware finds in South Lick, Indiana. And now, for a limited time, there's a new special featured on the menu—murder! Ever since meeting the wary owners of an antique shop opening across the street, Robbie has been scrambling to manage weird incidences plaguing her café and country store. Pricey items vanish from shelves without explanation, a fully equipped breakfast food truck starts lingering around the area each morning, and loyal diners mysteriously fall ill. When an elderly man dies after devouring an omelet packed with poisonous mushrooms, Robbie must temporarily close down Pans 'N Pancakes and search for the killer with a real zest for running her out of business—or else. Includes Recipes for You to Try!